CHARACTERIZATION AND CLASSIFICATION OF RICE GROWING SOILS OF SOUTHERN REGION OF TELANGANA STATE - V. PRAVEEN RAO, M. RAM PRASAD, CH. CHANDRA SEKHAR, P. RAVI, V. GOVERDHAN and (The Journal of Research, PJTSAU, 2019)
Ten representative pedons from rice-growing soils of southern Telangana region were characterized and classified. The soils were sandy loam to clay in texture with low permeability. The soils were neutral to slightly alkaline in reaction, low to high in organic carbon, mixed in mineralogy and moderately deep to deep. Bulk density increased with depth and values ranged from 1.26 to 1.81 Mg m-3. Water retentions at 33 kPa and 1500 kPa of soils ranged from 7.9 to 38.7% and 2.2 to 22.1%, respectively. Cation exchange capacity and soil pH followed no definite distribution pattern with depth. The available N was low to medium and available phosphorous and potassium were low to high. The available N, P and K decreased with depth. Based on soil characteristics, the soils of Chevella (P1), Thandur (P4), Shadnagar (P5), Palem (P6) and Narayanpuram (P9) were classified as Alfisols, soils of Ibrahimpatnam (P3), Jadcharla (P7) and Suryapeta (P8) were grouped under Inceptisols, soils of Gollapally (P10) were classified as Entisols and soils of Rajendranagar (P2) were under Vertisols